Training Need Assessment (TNA) : An analysis on the project ‘Improving Small Farmers’ Access to Markets in Maharashtra - G. Raja Shekar; Pradip Patil; Hemant ·Kumar Thakre; Aarti Pankhraj (Journal of Agricultural Extension Management, 2014)
This study assessed the training needs of lead farmers selected as part of the project on Improving Small Farmers Access to Market in Maharashtra. In all, 1400 lead farmers representing farmer groups in 8 districts of Maharashtra participated in the TNA. Data were collected by way of Focus Group Discussions. Training needs pertaining to Institutional building, Horticultural crop production, Post Harvest Management and Marketing were studied for designing need based training curriculum and training modules for capacity building of farmers